1967
DOI: 10.1038/2161229a0
|View full text |Cite
|
Sign up to set email alerts
|

Density Distribution Analysis of Antigen Sensitive Cells in the Rat

Abstract: Density distribution analysis is a convenient objective means of characterizing different cell populations (1)(2)(3)(4)(5)28). With most populations a prominent feature of this technique is a reproducible heterogeneity of components which is apparently not an artifact (3, 5). Attempts to understand this heterogeneity in terms of functional differences have been only partially successful; preliminary results have indicated that differences in density of 19S hemolysin-forming ceils reflect differences in physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1969
1969
1976
1976

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
2
0
0
Order By: Relevance
“…We have shown that the responding B cell subset 7 days after boost is enriched in the low density fractions of cells separated o n BSA density gradients. This finding is consistent with those of other workers [ 16,[38][39][40] who have found that the PFC precursors in very recently primed spleens are in a low density, proliferating cell population, whereas long-term memory lymphocytes have high density. We find a poor IgG response in vitro using high density cellsa population potentially contaminated with low density cellswhich tends t o confirm that memory cells d o not respond under these conditions, and that the responding IgG precursors arise by antigen stimulation of memory cells rather than by splenic recruitment.…”
Section: Discussionsupporting
confidence: 94%
“…We have shown that the responding B cell subset 7 days after boost is enriched in the low density fractions of cells separated o n BSA density gradients. This finding is consistent with those of other workers [ 16,[38][39][40] who have found that the PFC precursors in very recently primed spleens are in a low density, proliferating cell population, whereas long-term memory lymphocytes have high density. We find a poor IgG response in vitro using high density cellsa population potentially contaminated with low density cellswhich tends t o confirm that memory cells d o not respond under these conditions, and that the responding IgG precursors arise by antigen stimulation of memory cells rather than by splenic recruitment.…”
Section: Discussionsupporting
confidence: 94%
“…This result agrees with previous cell electrophoresis and adherence column studies in this laboratory (11,12) which characterized most of the unprimed AFC progenitors as atypically fast migrating and exceptionally adherent B cells. The earlier density separation studies of Haskill (37) and Haskill and Marbrook (38) are in general agreement with these conclusions. They are also consistent with recent findings of Strober (13) on the sedimentation characteristics of unprimed AFC progenitors in the rat.…”
Section: Effect Of Age Upon the Sedimentation Velocity Characteristics Of Igm Afc Progenitors Of Germfree Mouse Spleen Slow Sedimenting Dsupporting
confidence: 81%